Essai d’optimisation des procédés de fabrication du fromage traditionnel de qualité (jben) - GHALEM, IKrame (My University, 2025)
Among the traditional milk preparations in Algeria, “Jben” is produced using various methods across different regions. This study aims to evaluate the microbiological and physicochemical quality of raw milk and «Jben», by examining the effect of three natural substances: salt, thyme, and a low amount of salt. Three samples of «Jben» were prepared from raw cow's milk collected in Mostaganem. Physicochemical analyses showed a pH of 6.8 and a density of 25°D for the milk. The cheese samples exhibited a pH of 5.2 and a density of 75°D (with salt), a pH of 5.8 and a density of 66°D (with thyme), and a pH of 5.6 and a density of 81°D (with low salt). Microbiological analyses revealed contamination of both the milk and the «Jben» by microorganisms: total mesophilic aerobic flora (TMAF) > 10³, fungi > 10⁵, thermotolerant coliforms (TC) > 10³, and Enterobacteria > 10⁵. However, a notable reduction in this microbial flora was observed in the cheese samples: TC and total coliforms > 10², and Enterobacteria < 10⁵. Fecal contamination germs such as fecal coliforms and fecal streptococci were detected, as well as the presence of Staphylococcus aureus. No major pathogenic organisms (such as Salmonella or bacterial spores) were detected. These results can largely be attributed to poor hygiene practices on farms (e.g., dirty udders, contaminated equipment) as well as potential secondary contamination during laboratory handling. The tested natural substances showed varying effects on microbiological quality. Thyme was found to be relatively effective in limiting microbial proliferation and improving the sanitary quality of the final product.
Keywords: traditional cheese, Jben, quality improvement, salt, thyme